Molecular organization of central cholinergic synapses - Justin S. Rosenthal; Dean Zhang; Jun Yin; Caixia Long; George Yang; Yan Li; Zhiyuan Lu; Wei-Ping Li; Zhiheng Yu; Jiefu Li; Quan Yuan (Proceedings of the National Academy of Sciences, 2025)
Synapses have undergone significant diversification and adaptation, contributing to the complexity of the central nervous system. Understanding their molecular architecture is essential for deciphering the brain’s functional evolution. While nicotinic acetylcholine receptors (nAchRs) are widely distributed across metazoan brains, their associated protein networks remain poorly characterized. Using in vivo proximity labeling, we generated proteomic maps of subunit-specific nAchR interactomes in developing and mature Drosophila brains. Our findings reveal a developmental expansion and reconfiguration of the nAchR interactome. Proteome profiling with genetic perturbations showed that removing individual nAchR subunits consistently triggers compensatory shifts in receptor subtypes, highlighting mechanisms of synaptic plasticity. We also identified the Rho-GTPase regulator Still life (Sif) as a key organizer of cholinergic synapses, with loss of Sif disrupting their molecular composition and structural integrity. These results provide molecular insights into the development and plasticity of central cholinergic synapses, advancing our understanding of synaptic identity conservation and divergence.